KEMAMPUAN ADSORPSI BATU PASIR YANG DILAPISI BESI OKSIDA (Fe2O3) UNTUK MENURUNKAN KADAR Pb DALAM LARUTAN - Dewi, I.G.A. Kunti Sri Panca (Bumi Lestari, 2009)
The capability of sandstone coated with Fe2O3 as adsorbent to reduce lead (Pb) content in solution has been stadied in this research. The adsorption process of Pb in solution by sandstone was carried out by immersing sandstone (uncoated A0) in Pb(NO3)2. Coating sandstone was done using Fe(NO3)3.9 H2O with different concentration as follows : 10 g (A1), 20 g (A2) and 30 g (A3) in 50 ml aquadest. To find out the optimum concentration of Fe(NO3)3 as coating agent. The adsorption process of coated sandstone was done by immersing them in Pb(NO3)2 solution. To determine the time of optimum adsorption, the sandstone (coated and uncoated) were immersed for a period of their equilibrium adsorption time. The absorbance of the filtrat resulted from adsorption process was determined by atomic absorption spectrophotometer at ? 217 nm. The result showed that optimum concentration of Fe(NO3)3 as coating agent was 20 g (A2) with the capability absorbing lead (Pb) 4.653 mg/g. The capability of A3 as adsorbent was 4.644 mg/g and the capability of A1 was 4.529 mg/g while the capability uncoated sandstone as adsorbent was 2.784 mg/g.
Keywords: sandstone; adsorption; equilibrium time; optimum concentration